HUBUNGAN ANTARA KONSUMSI KOPI TERHADAP DISMENORE PADA MAHASISWI FAKULTAS KEDOKTERAN UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA - Elvina Damayanti, (2022)
Background. Dysmenorrhea is a painful condition during menstruation and is the most common gynecological complaint in the world. The condition of dysmenorrhea in women causes weakness and discomfort in daily activities. Medical students are in the age range prone to dysmenorrhea and have a high study load, which triggers them to stay awake by consuming coffee. Moreover, caffeine can worsen dysmenorrhea. Objective. This study aims to determine the relation between coffee consumption and dysmenorrhea in students of the Faculty of Medicine, Universitas Pembangunan Nasional Veteran Jakarta. Method. This study was an analytical observation with a cross-sectional research design with 62 respondents and simple random sampling method. The questionnaire consisted of personal data, coffee consumption questionnaire, and Working ability, Location, Intensity (Wong-Baker), Days of pain, and Dysmenorrhea (WaLIDD) questionnaires. Data analysis in this study used the Fisher exact test. Results. The results of this study found that there was no relation (p = 0.748) between coffee consumption and dysmenorrhea. Discussion. This can be caused by other factors that cause dysmenorrhea and caffeine levels in coffee which depend on the type of coffee consumed and the frequency of drinking coffee. Conclusion. There was no relation between coffee consumption and dysmenorrhea in the Faculty of Medicine students, Universitas Pembangunan Nasional Veteran Jakarta. Keywords: dysmenorrhea, coffee consumption, female students